The Analysis of The Implementation of The Coronavirus Disease-2019 Vaccination Policy In Indonesia (Case Study of West Java Province) - Marion Siagian (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The COVID-19 vaccination program constitutes a key government policy to mitigate virus transmission and support public health and socio-economic recovery. Despite its strategic importance, the implementation of the vaccination policy in Indonesia has encountered persistent challenges. This study examines the implementation of the COVID-19 vaccination policy in Indonesia, with a particular focus on West Java Province, to assess its effectiveness and identify key constraints affecting policy outcomes. Employing a qualitative descriptive approach, this study is based on a systematic review of academic literature, policy documents, and official government reports related to the national and regional vaccination programs. The findings reveal that during the early phase of implementation, the vaccination policy was insufficient to effectively control the COVID-19 pandemic, as reflected in the surge of cases between June and August 2021, indicating that herd immunity had not yet been achieved, including in West Java Province. While vaccination strategies in Indonesia and other countries are fundamentally grounded in the herd immunity framework, policy effectiveness is strongly shaped by the prioritization of high-risk populations, social dynamics influencing vaccine acceptance, vaccine availability, health system capacity, and the emergence of new virus variants. This study contributes to the literature on public health policy implementation by highlighting structural and contextual factors that constrain vaccination outcomes in decentralized governance settings and offers insights for designing more adaptive and resilient vaccination policies in future public health emergencies.